2020
DOI: 10.3390/cells9010258
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Roles of Fox Family Transcription Factors in Chromosome Replication, Organization, and Genome Stability

Abstract: The forkhead box (Fox) transcription factors (TFs) are widespread from yeast to humans. Their mutations and dysregulation have been linked to a broad spectrum of malignant neoplasias. They are known as critical players in DNA repair, metabolism, cell cycle control, differentiation, and aging. Recent studies, especially those from the simple model eukaryotes, revealed unexpected contributions of Fox TFs in chromosome replication and organization. More importantly, besides functioning as a canonical TF in cell s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…These are the Fkh, highly conserved transcription factors in eukaryotes, from yeast to human, with roles in physiological processes and diseases. Human Fkh molecules have been intensively studied due to their crucial function in cellular processes such as cell cycle regulation 66 , 67 , genome replication and stability 68 , aging and oxidative stress 69 , 70 , metabolism 71 , 72 , cancer 73 76 , and neurodegeneration 77 . The human Fkh family comprises 18 subfamilies 78 , 79 , with two of them named Forkhead box O (FoxO) and M (FoxM) being the closest functional counterpart of the budding yeast Fkh1 and Fkh2.…”
Section: Introductionmentioning
confidence: 99%
“…These are the Fkh, highly conserved transcription factors in eukaryotes, from yeast to human, with roles in physiological processes and diseases. Human Fkh molecules have been intensively studied due to their crucial function in cellular processes such as cell cycle regulation 66 , 67 , genome replication and stability 68 , aging and oxidative stress 69 , 70 , metabolism 71 , 72 , cancer 73 76 , and neurodegeneration 77 . The human Fkh family comprises 18 subfamilies 78 , 79 , with two of them named Forkhead box O (FoxO) and M (FoxM) being the closest functional counterpart of the budding yeast Fkh1 and Fkh2.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 It is reported that FOXL1 is involved in the TGF-p1 signaling by targeting Smad2, BMP-7, and TGF-131. 21,22 FOXL1 is a transcription factor expressed in mesenchymal cells of the gastrointestinal tract. The homology of the Forkhead region with FOXL1 at nucleotide level is as high as 83%, suggesting that FOXL1 may be involved in the regulation of TGFβ/Smads signaling, and thus participates in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…This sequence was very similar to the consensus GLISBS reported previously 32, 46, 47 , indicating that our ChIP-Seq was successful in detecting specific GLIS1 binding sequences. Our GLIS1 ChIP-Seq analysis identified a number of additional motifs, including motifs for bZIP transcription factors (e.g., ATF3, FRA1, BATF, and JUNB, members of the AP-1 complex), forkhead box (FOX) proteins 48 , and TEA domain transcription factors (TEAD) that play a key role in the Hippo pathway 49 . These data suggested co-localization of the GLIS1 binding consensus with motifs for other transcription factors that have been previously implicated in the regulation of TM and glaucoma 45, 50, 51 .…”
Section: Resultsmentioning
confidence: 99%